2015
DOI: 10.1002/adma.201501939
|View full text |Cite
|
Sign up to set email alerts
|

An Amorphous Carbon Nitride Photocatalyst with Greatly Extended Visible‐Light‐Responsive Range for Photocatalytic Hydrogen Generation

Abstract: Amorphous carbon nitride (ACN) with a bandgap of 1.90 eV shows an order of magnitude higher photocatalytic activity in hydrogen evolution under visible light than partially crystalline graphitic carbon nitride with a bandgap of 2.82 eV. ACN is photocatalytically active under visible light at a wavelength beyond 600 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
488
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 837 publications
(518 citation statements)
references
References 38 publications
29
488
1
Order By: Relevance
“…31 Additionally, a reduced optical gap of PCN at 1.90 eV was reported for an amorphous PCN. 32 In order to be suitable for practical applications, it has been predicted that E opt g has to lie between 1.8 and 2.1 eV to meet the targeted ∼10 % solar to hydrogen efficiency. 33 Hence, to further exploit the photocatalytic efficiency of PCNs, an understanding of the underlying parameters affecting the optical properties of PCNs is highly desirable.…”
Section: Refining the Methodologymentioning
confidence: 99%
“…31 Additionally, a reduced optical gap of PCN at 1.90 eV was reported for an amorphous PCN. 32 In order to be suitable for practical applications, it has been predicted that E opt g has to lie between 1.8 and 2.1 eV to meet the targeted ∼10 % solar to hydrogen efficiency. 33 Hence, to further exploit the photocatalytic efficiency of PCNs, an understanding of the underlying parameters affecting the optical properties of PCNs is highly desirable.…”
Section: Refining the Methodologymentioning
confidence: 99%
“…The increase in the band gap by 0.10 eV improves the redox ability of the charge carriers generated in the CN nanosheets. 40 This result was further conrmed by the blue-shi in its uorescence emission peak in Fig. 6b; this could be attributed to the quantum connement effect.…”
Section: Optical Propertiesmentioning
confidence: 86%
“…However, the two sharp peaks become very weak in the U-N pattern, which demonstrate the absence of long-range order in the atomic arrangements. 40,41 We may infer the multiple effects of too many gas bubbles, which are produced during thermal condensation of urea, and the additional N 2 signicantly disrupts the longrange atomic order in both the perpendicular and parallel directions to the g-C 3 N 4 layers. Aer stopping the addition of N 2 , the self-producing atmosphere originates from the interior of the reaction system.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…The covalent bonds are more resistant to rupture than vdW and hydrogen bonds that offer a possibility of disrupting long‐range, but keeping short‐range, atomic order for homogeneous amorphization upon heating PCN at elevated temperature. Kang et al reported ACN with a band gap of 1.90 eV 25. Following this, we worked on ameliorating the charge transfer kinetics of ACN to overcome its low quantum yield (<0.5%) for hydrogen production 54…”
Section: Selective Techniques For Tuning Intrinsic Properties Of Cnmentioning
confidence: 95%
“…Besides polycrystalline GCN, amorphous carbon nitride (ACN) has also been reported to be a promising photocatalyst 25, 26, 27. Varying the C/N ratio, two eminent derivatives of carbon nitride, namely, C 2 N28 and C 3 N29 have been reported, which might also possibly be used as a photocatalyst.…”
Section: A Brief Overview Of Carbon Nitridesmentioning
confidence: 99%